A Comparative Analysis of Whistleblower’s Protection in Indonesia and United States of America - Rahardjo, Benjamin S. (Bina Nusantara University, 2017)
The researcher classified whistleblowing system, its protection in Indonesia, and compared it with practices in the United States of America (USA). The researcher used the qualitative descriptive method with secondary data, such as legislation, news, articles from competent internet sources, journals, books and presentation materials that related to whistleblowers. It finds that whistleblowing has been proven as one of most effective way to nurture good corporate government. On the other hand, it demands the proper protection for its blowers. This research suggested Indonesian government to improve whistleblowing system through comprehensive legislations and coordination among related institutions. Witness and Victim Protection Agency (Lembaga Perlindungan Saksi dan Korban/LPSK) have a vital role in improving support for the reporters.